Surgical treatment of the ischemic heart disease with lowered contractility of left ventricle and mitral valve insufficiency - S. A. Rudenko; A. V. Rudenko; Yu. V. Kaschenko; V. P. Zakharova (Клінічна хірургія)
Objective. To determine the impact of the mitral valve insufficiency in patients, suffering ischemic heart disease with lowered contractility of left ventricle and methods of its treatment.